The effectiveness of orthodontic treatment with clear aligners in different thicknesses - Saniye Merve Cengiz; Merve Goymen (Scientific Reports)
Abstract This study aimed to evaluate the effectiveness, pain, and satisfaction levels of patients treated with different thicknesses of clear aligners among class I maxillary mild crowding cases. Twenty-eight subjects were randomly divided into two groups. Group 1 were treated with 0.5 mm-thick aligners and group 2 were treated with 0.75 mm-thick aligners. Maxillary models were printed using a 3-dimensional printer and aligners were produced using a vacuum thermoforming machine. The amount of orthodontic tooth movement was evaluated by comparing pre- and post-treatment digital models and lateral cephalograms taken at the beginning and end of the treatment. Pain and satisfaction levels were measured before aligner insertion, at the 4th hour, 2nd day, 1st week, 1st month and at the end of the treatment. Increases in maxillary intercanine, interpremolar, and intermolar widths, and dental arch perimeter were significantly higher in group 2 (p < 0.05). The pain levels peaked at T1 and decreased gradually in both groups; group 2 demonstrated greater pain levels. Group 1 reported significantly greater satisfaction levels (p < 0.05). Aligner thickness is a key determinant of the extent of orthodontic tooth movement. Treatment with a 0.5 mm-thick aligner provides enhanced comfort for patients, but a 0.75 mm-thick aligner yields more efficient treatment results. Trial registration: The trial was registered on https://ClinicalTrials.gov retrospectively with the registration number of NCT06504498, on 16/07/2024.